157k views
1 vote
Anyone know how to do this?

Anyone know how to do this?-example-1

2 Answers

3 votes
f(x)=x² - 8x + 15,
15=(-3)*(-5), -3+(-5)=-8
f(x)=x² - 8x + 15 = (x-3)(x-5)

g(x)=x-3

h(x)=f(x):g(x)


h(x)= ((x-3)(x-5))/(x-3) = x-5, h(x)=x-5 Denominator cannot be equal 0. x-3=0, x=3

Domain of h(x) is (-∞,3) U (3, +∞)
User Pinxue
by
4.8k points
4 votes
h(x) = x - 5

However, it had a domain of all real numbers such that x does not equal 3, since that would cause you to divide by 0.
User CharlesDeeZee
by
5.9k points